2014
DOI: 10.1016/j.fgb.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The protein phosphatase PhzA of A. fumigatus is involved in oxidative stress tolerance and fungal virulence

Abstract: Protein phosphatases Z that are unique to the fungal kingdom have been associated to resistance to high salt concentration, cell wall integrity, cell cycle regulation, and oxidative stress in fungi. In Aspergillus fumigatus it was shown that PHZA is under the control of the transcription factor Skn7 and is only involved in the control of the oxidative stress. Accordingly, the ΔphzA mutant showed a defect in virulence in an experimental model of corneal infection in immunocompetent animals and that the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…In C. albicans , the lack of PPZ1 led to impaired virulence in a mouse model (Ádám et al ., ). In A. fumigatus , deletion of PPZA also showed a defect in virulence in a murine model of corneal infection (Muszkieta et al ., ). However, in this study, ΔFgPPZ1 (ΔFg00852) did not show any detectable defects in virulence.…”
Section: Discussionmentioning
confidence: 98%
“…In C. albicans , the lack of PPZ1 led to impaired virulence in a mouse model (Ádám et al ., ). In A. fumigatus , deletion of PPZA also showed a defect in virulence in a murine model of corneal infection (Muszkieta et al ., ). However, in this study, ΔFgPPZ1 (ΔFg00852) did not show any detectable defects in virulence.…”
Section: Discussionmentioning
confidence: 98%
“…The calcineurin phosphatase is central to calcium signaling and plays an important role in determining fungal cell morphology and virulence (Steinbach et al, 2007). In human (Candida albicans, Cryptococcus neoformans, and Aspergillus fumigatus) and plant pathogens (Fusarium spp., Sclerotinia sclerotiorum, Ustilago maydis, Magnaporthe oryzae and Botrytis cinerea), other protein phosphatases have been described as regulating mating, asexual development, differentiation, cation homeostasis, CWI, oxidative stress, virulence and pathogenicity (Erental et al, 2007;Di Stasio et al, 2009;Feng et al, 2010;Jiang et al, 2011;Adám et al, 2012;Du et al, 2013;Shin et al, 2013;Yang et al, 2013a,b;Lee et al, 2014;Muszkieta et al, 2014;Yu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we demonstrated that the PpzA was important for A. fumigatus virulence in a low-dose murine infection model. Similarly, a previous study reported that the ppzA mutant showed a defect in virulence in an experimental model of corneal infection in immunocompetent animals (Muszkieta et al, 2014). In Candida albicans, the lack of PPZ1 causes impaired virulence in a mouse virulence model (Adám et al, 2012).…”
Section: Analysis Of Chromosomal Patterns Of Gene Expression Inmentioning
confidence: 77%
“…fumigatus protein phosphatase null mutants that are associated to iron assimilation because they have reduced growth during iron starvation (Winkelströter et al, ). Among these protein phosphatases, we have identified the gene ppzA that codes for the catalytic subunit of PPZ and it was previously shown to be involved in oxidative stress tolerance (Leiter et al, ; Muszkieta et al, ). Here, we investigated the role played by PpzA during iron assimilation by using a combined transcriptomic and proteomic analysis comparing the corresponding wild‐type strain with ∆ ppzA mutant under iron starvation conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation